Nutritive value and organoleptic evaluation of Thamara Venda Genotypes (Abelmorchus Caillei) - Sona Thampy K (Department of Home Science, College of Horticulture, 1998)
The study on "Nutritive value and organoleptic evaluation of Thamara venda (Abelmoschus caillei) genotypes" was an assessment of the chemical composition and acceptability of Thamara venda genotypes in comparison with the okra variety, Pusa Sawani, at three different maturity levels i.e. 5th, 8th and 11 th days after flowering. It has been found in the study that the twenty genotypes of A. caillei differed very much in their chemical composition. In the case of fat, iron, vitamin C and mucilage, the mean values of the control variety were lower than the lowest obtained for A. caillei genotypes. Pusa Sawani was found to have a lower disposition in the case of total carbohydrates, starch and calcium contents in comparison with the Thamara venda genotypes. The mean moisture,• protein and phosphorus contents of Pusa Sawani were found to be in comparison with those of Thamara vend a genotypes. But in crude fibre content, Pusa Sawani outweighed the Thamara vend a genotypes. Statistically, it had been found that there was no concordance between the different genotypes of A. caillei in the case of different chemicl constituents. The present study also implicated significant decreases in moisture, protein, fat, calcium, phosphorus, iron and ascorbic acid contents of the pods as the days after flowering increased in both